Exciton Diffusion Length and Charge Extraction Yield in Organic Bilayer Solar Cells. Issue 12 (1st February 2017) - Siegmund, Bernhard; Sajjad, Muhammad T.; Widmer, Johannes; Ray, Debdutta; Koerner, Christian; Riede, Moritz; Leo, Karl; Samuel, Ifor D. W.; Vandewal, Koen
Abstract : A method for resolving the diffusion length of excitons and the extraction yield of charge carriers is presented based on the performance of organic bilayer solar cells and careful modeling. The technique uses a simultaneous variation of the absorber thickness and the excitation wavelength. Rigorously differing solar cell structures as well as independent photoluminescence quenching measurements give consistent results.